Inherited germline ATRX mutation in two brothers with ATR‐X syndrome and osteosarcoma. Issue 5 (28th March 2017) - Ji, Jianling; Quindipan, Catherine; Parham, David; Shen, Lishuang; Ruble, David; Bootwalla, Moiz; Maglinte, Dennis T.; Gai, Xiaowu; Saitta, Sulagna C.; Biegel, Jaclyn A.; Mascarenhas, Leo
Abstract : We report a family in which two brothers had an undiagnosed genetic disorder comprised of dysmorphic features, microcephaly, severe intellectual disability (non‐verbal), mild anemia, and cryptorchidism. Both developed osteosarcoma. Trio exome sequencing (using blood samples from the younger brother and both parents) was performed and a nonsense NM_000489.4:c.7156C>T (p.Arg2386*) mutation in the ATRX gene was identified in the proband (hemizygous) and in the mother's peripheral blood DNA (heterozygous). The mother is healthy, does not exhibit any clinical manifestations of ATR‐X syndrome and there was no family history of cancer. The same hemizygous pathogenic variant was confirmed in the affected older brother's skin tissue by subsequent Sanger sequencing. Chromosomal microarray studies of both brothers' osteosarcomas revealed complex copy number alterations consistent with the clinical diagnosis of osteosarcoma. Recently, somatic mutations in the ATRX gene have been observed as recurrent alterations in both osteosarcoma and brain tumors. However, it is unclear if there is any association between osteosarcoma and germline ATRX mutations, specifically in patients with constitutional ATR‐X syndrome. This is the first report of osteosarcoma diagnosed in two males with ATR‐X syndrome, suggesting a potential increased risk for cancer in patients with this disorder.